Mendefinisikan Kembali Konsep Keamanan dalam Agenda Kebijakan Negara-Bangsa - Azizah, RR Zahroh Hayati (Universitas Perrtahanan Indonesia (UNHAN), 2020)
Security is essential for the state. The state is said to be safe if it is free from threats. The definitionof security experienced a shift marked by the end of the Cold War and the tragedy of 11 September2001. The change in the concept of security, which was initially limited to military threats andaimed at the state, has now developed into a threat to human security. The purpose of this articleis to redefine the concept of security itself in the policy agenda of the Nation-State. The methodused is qualitative, using textual analysis as a data collection method.Keywords: Security, Threat, Policy